Effects of a Customs Union on Economic Growth: Empirical Evidence from Southern African Customs Union (SACU) - Lee, Han-Sol; Chernikov , Sergey U.; Moseykin , Yury N.; Barrie , Gibrilla (Economy of Regions, 2024)
This study analyses the effects of the Southern African Customs Union (SACU) on the economic growth of its member states based on unbalanced panel datasets. This research was inspired by the ongoing discussions about the development of “free-trade agreements” and the growing anxiety about the US dollar’s stability as a world currency. The latter has recently led to the announcement of the Brazil-Argentina currency union to make bilateral trade easier. As the SACU countries are practically using the South African Rand as a single currency, a growing interest in evaluating the SACU internal trade validity for being the foundation of similar integrative action has started to manifest. The regression results of pooled ordinary least squares (OLS), fixed effects (FE), and random effects (RE) models demonstrate that the economic growth effects of intra-trade (exports, imports) of SACU do not exist. This indicates that further economic integration may not provide positive effects for SACU. However, the most crucial factor to drive the economic growth of SACU turned out to be domestic investment. Attracting foreign direct investment (FDI) also highly contributes to the economic growth of SACU. It is natural and advisable for the member states of SACU to continue the enhancement of investment-conducive environments for domestic and foreign companies. In addition, the long-term fuelling of economic growth with government debt, government spending, and investments points to possible discrepancies in the economic structure of the union, may be connected to internal demand issues. In this sense, it would be reasonable to research the potential of expanding SACU to the countries of the Southern African Development Community (SADC).